2 Ways to Solve:
Solve by Square Roots:
2(x + 4)^2 + 4 = 02(x+4)2+4=0
2(x+4)^2 = -42(x+4)2=−4
(x + 4)^2 = -2(x+4)2=−2
(x + 4) = +- sqrt(-2)(x+4)=±√−2
x = -4 +- isqrt(2)x=−4±i√2
Using Quadratic Formula:
Need to multiply out first
y = 2(x +4)^2 + 4y=2(x+4)2+4
y = 2(x+4)(x+4) + 4y=2(x+4)(x+4)+4
y = 2(x^2 + 8x + 16)+4y=2(x2+8x+16)+4
y = 2x^2 + 16x + 32 + 4y=2x2+16x+32+4
y = 2x^2 + 16x + 36y=2x2+16x+36
x = (-b +- sqrt(b^2 -4ac))/(2a)x=−b±√b2−4ac2a
x = (-(16) +- sqrt((16)^2 - 4(2)(36)))/(2(2))x=−(16)±√(16)2−4(2)(36)2(2)
x = (-16 +- sqrt(256-288))/4x=−16±√256−2884
x = (-16 +- sqrt(-32))/4x=−16±√−324
x = (-16 +- 4isqrt(2))/4x=−16±4i√24
x = -4 +- isqrt(2)x=−4±i√2